Oxylipins From Different Pathways Trigger Mitochondrial Stress Signaling Through Respiratory Complex III - Izquierdo, Yovanny; Muñiz, Luis; Vicente, Jorge; Kulasekaran, Satish; Aguilera, Verónica; López Sánchez, Ana; Martínez-Ayala, Ada; López, Bran; Cascón, Tomás; Castresana, Carmen (Frontiers in Plant Science, 2021)
Plant oxylipins are signaling molecules produced from fatty acids by oxidative pathways, mainly initiated by 9- and 13-lipoxygenases (9-LOX and 13-LOX), alpha-dioxygenases or non-enzymatic oxidation. Oxylipins from the 9-LOX pathway induce oxidative stress and control root development and plant defense. These activities have been associated with mitochondrial processes, but precise cellular targets and pathways remain unknown. In order to study oxylipin signaling, we previously generated a collection of Arabidopsis thaliana mutants that were insensitive to the 9-LOX products 9(S)-hydroxy-10,12,15-octadecatrienoic acid (9-HOT) and its ketone derivative 9-KOT (noxy mutants). Here, we describe noxy1, noxy3, noxy5, noxy23 and noxy54 mutants, all affected in nucleus-encoded mitochondrial proteins, and use them to study the role of mitochondria in oxylipin signaling. Functional and phenotypic analyses showed that noxy plants displayed mitochondrial aggregation, reduced respiration rates and resistance to the complex III inhibitor Antimycin A (AA), thus indicating a close similarity of the oxylipin signaling and mitochondrial stress. Application of 9-HOT and 9-KOT protected plants against subsequent mitochondrial stress, whereas they boosted root growth reduction when applied in combination with complex III inhibitors but did not with inhibitors of other respiratory complexes. A similar effect was caused by linear-chain oxylipins from 13-LOX or non-enzymatic pathways having α,β-unsaturated hydroxyl or keto groups in their structure. Studies to investigate 9-HOT and 9-KOT activity indicated that they do not reduce respiration rates, but their action is primarily associated with enhanced ROS responses. This was supported by the results showing that 9-HOT or 9-KOT combined with AA amplified the expression of oxylipin- and ROS-responding genes but not of the AA marker AOX1a, thus implying the activation of a specific mitochondria retrograde signaling pathway. Our results implicate mitochondrial complex III as a hub in the signaling activity of multiple oxylipin pathways and point at downstream ROS responses as components of oxylipin function.